2020
DOI: 10.1177/1350650120920503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interconnected metal skeletons on the tribological properties of polyurethane elastomers

Abstract: Electrostatic cumulative discharges from the surfaces of polyurethane elastomers are often the primary cause of accidents and disasters, such as equipment failures, fires, and explosions, in industries. In this study, in order to improve the electrostatic protection performance of PU as well as to enhance the wear resistance of the PU matrix, copper foam was embedded in polyurethane to form a copper foam-based polyurethane composite with a three-dimensional connected metal skeleton. The mechanical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The results show that the hardness plays an important role in the fracture sensitivity of PUR material, and in a certain hardness range, PUR with higher hardness has higher toughness, wear resistance, and fatigue resistance. Wen et al [ 10 ] found that electrostatic cumulative discharges on the surfaces of PU elastomers could lead to accidents and disasters, such as equipment failures, fires, and explosions, in industries. In order to solve this problem, they adopted the method of embedding copper foam in PU to form a copper foam-based PU composite, which greatly improved the electrostatic protection performance and wear resistance of PU.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the hardness plays an important role in the fracture sensitivity of PUR material, and in a certain hardness range, PUR with higher hardness has higher toughness, wear resistance, and fatigue resistance. Wen et al [ 10 ] found that electrostatic cumulative discharges on the surfaces of PU elastomers could lead to accidents and disasters, such as equipment failures, fires, and explosions, in industries. In order to solve this problem, they adopted the method of embedding copper foam in PU to form a copper foam-based PU composite, which greatly improved the electrostatic protection performance and wear resistance of PU.…”
Section: Introductionmentioning
confidence: 99%